If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 6x = 12x + -7 Reorder the terms: 6x + y = 12x + -7 Reorder the terms: 6x + y = -7 + 12x Solving 6x + y = -7 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 6x + -12x + y = -7 + 12x + -12x Combine like terms: 6x + -12x = -6x -6x + y = -7 + 12x + -12x Combine like terms: 12x + -12x = 0 -6x + y = -7 + 0 -6x + y = -7 Add '-1y' to each side of the equation. -6x + y + -1y = -7 + -1y Combine like terms: y + -1y = 0 -6x + 0 = -7 + -1y -6x = -7 + -1y Divide each side by '-6'. x = 1.166666667 + 0.1666666667y Simplifying x = 1.166666667 + 0.1666666667y
| 30=10(x)+6(x) | | 3y-6=4y | | 4x-24+3x=6x+1 | | 8y=-6x+4 | | 15y=-4-5(1/5) | | 5(n-2)=0 | | x^3=2x^2+3x | | x+x+40+x-50=90 | | 95-73=x | | 2(x-3)+5(-x)=2(-x)-4 | | 3(3+w)=2(w-6) | | 360=x+x-35+.5x+x-46 | | 10/x-2=2 | | X/4-2=16 | | 5y-5+y+31=5y+30-3y | | 0=6t^2-30t+36 | | 2(k+1)-(7+6k)=-5k | | 24-7x=13+4x | | ln(4x-2)+ln(9-3x)=2ln(x+1) | | 2/3y-8=1/6 | | 37-8=X | | (14+2x)(18+2x)=228 | | -3=9+x | | -3=9+8 | | y=8ln(5x) | | (-8)8= | | 5(2a-3)-6(a+2)=-7 | | x/8-12=-23 | | 8.95-21.35=X | | 11/3-2/3= | | 4v(2v+10v)=0 | | -4(y-3)+2(3y-5)=11 |